2020
DOI: 10.1101/2020.03.11.20034389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pan-resistome characterization of uropathogenic Escherichia coli and Klebsiella pneumoniae strains circulating in Uganda and Kenya isolated from 2017-2018

Abstract: Background: Urinary tract infection (UTI) develops after a pathogen adhered to the inner lining of the urinary tract. Cases of UTIs are predominantly caused by several Gram-negative bacteria and account for high morbidity in the clinical and community settings. Of greater concern are the strains carrying antimicrobial resistance (AMR)-conferring genes. The gravity of UTI is also determined by a spectrum of other virulence factors. This study represents a pilot project to investigate the burden of AMR among uro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…For library preparation, the extracted DNA was end-repaired using the NEBNext® UltraII End Repair/dA-Tailing kit using the manufacturer's instructions. LSK 109 ligation kit, EXP-NBD 104 (1-12), and EXP-NBD 114 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Native Barcoding kits were used to barcode each DNA sample and adapters added. The DNA library was loaded onto a FLO-MIN106 R9.…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…For library preparation, the extracted DNA was end-repaired using the NEBNext® UltraII End Repair/dA-Tailing kit using the manufacturer's instructions. LSK 109 ligation kit, EXP-NBD 104 (1-12), and EXP-NBD 114 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) Native Barcoding kits were used to barcode each DNA sample and adapters added. The DNA library was loaded onto a FLO-MIN106 R9.…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
“…In Kenya, several studies have indicated an emergence of the clonal spread of MDR KP and horizontal transfer of AMR genes (6,(12)(13)(14)(15). Increased use of 3rd generation cephalosporins in the early 2000s has increased extended-spectrum beta-lactamase (ESBL)-producing Enterobacterales, the most prevalent of which in Kenya are CTX-M-15 and SHV (10,12,16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine samples were analysed using culture and antibiotic sensitivity testing (C&AST), and a total of 150 bacterial isolates (n=91 from Kenya and n=59 from Uganda) were genomically characterised, which confirmed a high prevalence of uropathogenic strains Escherichia coli and Klebsiella pneumoniae , and revealed high levels of multidrug resistance mainly disseminated via clonal and horizontal transfers (the full results are reported here 28 ). This exploratory pilot study illustrated the feasibility of collecting linked microbiological, genomic and socioeconomic data, and highlighted important operational fieldwork issues regarding linkage and follow-up to the homestead.…”
Section: Introductionmentioning
confidence: 98%
“…HATUA pilot activities in 2017-18 in Uganda demonstrated the feasibility of the holistic approach by conducting a study of microbiological and genomic features of urinary pathogens collected from clinic patients, combined with quantitative socio-demographic data. Genomic characterisation of the strains (predominantly E. coli and K. pneumoniae ) revealed high levels of resistance mainly disseminated via clonal and horizontal transfer [28]. We also conducted in-depth interviews with patients and healthcare providers, and focus group discussions with community members in Mbarara district, Uganda to explore behaviours and attitudes to AB use.…”
Section: Introductionmentioning
confidence: 99%